A FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN POSTPARTUM BLUES - Junie Harista; Rama Agustina (IKesT Muhammadiyah Palembang, 2023)
ABSTRACT Introduction: One of the health development priorities in developing countries, especially Indonesia, is improving maternal and child health. This development is directed at the physical and mental health of the mother starting from the period of pregnancy, childbirth and postpartum. Pregnancy and childbirth are normal events that occur in life, but many mothers experience stress due to the demands of adjustment due to changes in life. Objective: to determine the factors influencing the occurrence of Postpartum blues. Methods: The design of this research was an analytic survey with a cross sectional approach. The population in this study was all postpartum mothers who visited during the research and the sampling technique used accidental sampling. Results: The study obtained a p value = 0.003 <0.05, so HO was rejected, meant that there was a relationship between age and the occurrence of postpartum blues. Value = 0.017 <0.05, so HO was rejected, meant that there was a relationship between parity and the occurrence of postpartum blues and obtained p value value = 0.613> 0.05 then HO was accepted, meant that there was no relationship between education and the occurrence of postpartum blues. Conclusion: It is expected that health workers will improve communication of information and education (IEC) about postpartum blues in various media so that they can increase the knowledge of mothers or the community Keywords : Postpartum blues, Age, Parity and Education